Marcadores discursivos na aquisição do português como língua adicional : uma aplicação da análise da conversa em amostras do Brasil e da Inglaterra - Quadros, Thais Dias de (2019)
Discursive markers (DMs) have been presented as a concern of linguists, especially those who address issues pertaining to Conversation Analysis (CA) or interactions performed orally in general. Due to the fact that DM studies are numerous and set different perspectives in relation to the same research object, it is necessary to build a cutout of the most influential strands of these studies. Based on this primary need, this dissertation explores three perspectives: Schiffrin's Discourse (1987, 1994), Fraser's Pragmatics (1990, 2009) and Maschler's Interactional Linguistics (1991, 1994, 1997, 2012), seeking to understand their definitions of DM and their respective analytical methodologies. From these fundamental studies, we rely on the body of research referring to DMs in pedagogical context by Fung & Carter (2007) and Risso and colleagues (2002) for the creation of a delimiting framework of "DM" units and of functional frameworks to which these DMs apply in a classroom context. In order to analyze interaction samples in classrooms of Portuguese as an Additional Language (PAL), from Brazil and from England, we rely on the fundamentals of AC - in such a way that it is possible to be closer to the phenomenon at the time of analysis (Ten Have, 2007), and we use the software CLAN - which organizes the data with the CA conventions, developed by Jefferson (1972). From this standpoint, this research brings to light the DM produced in the spontaneous speech of PAL learners, the functional categories to which they belong, and different DM and/or DM uses presented in the contrast between apprentices in Brazil and in England. By the end of this study, it was possible to elaborate a set of 71 DM, which belong to four different functional categories, in the PLA classrooms investigated.